Can philosophy be incorporated in Caxias? and the voices of children from the periphery - Gomes, Vanise Cássia Araújo Dutra (Universidad Pedagógica y Tecnológica de Colombia, 2019)
This text reflects on questions arising from the displacements associated with a philosophical project entitled Can philosophy be incorporated in Caxias? The public school bets on thinking, which is carried out with children from a public school located on a periphery in Brazil. This is a university extension project implemented by State University of Rio de Janeiro [UERJ in its Portuguese acronym]. It is coordinated by the Philosophy and Children Studies Group from the master’s program in Education at UERJ and it is developed in Municipal School Joaquim da Silva Peçanha in the municipality of Duque de Caxias in Rio de Janeiro; my workplace. We will try to make a brief foray into living this enigmatic exercise in a territory where the intention is to think about philosophy outside the university walls; a peripheral place where philosophy seems to have always been missing. However, when present, it affirms students’ and teachers’ strong, unique, and different voices as well as their thoughts on children in a Brazilian public school.